Playground Quality Assessment with Weighted Criteria Method: Elazığ Culture Park Case - Unal, Muge; Cevik, Muhammed Bekir (Springer, 2025)
Play is a fundamental component of children's well-being, shaping their physical, cognitive, and socio-emotional development. Playgrounds act as essential environments that foster creativity, social interaction, and motor skill enhancement. This study evaluates the suitability of two playgrounds in Elaz & imath;& gbreve;'s K & uuml;lt & uuml;r Park using the Weighted Criteria Method, a structured framework that assesses playground quality through predefined well-being indicators. The research follows four key stages: (1) defining evaluation criteria within five main categories, including Play Equipment and Surface, Auxiliary Equipment, Design Characteristics, Safety, and Vandalism; (2) determining criteria weighting based on expert opinions; (3) conducting field studies and scoring criteria to assess the playgrounds' suitability for different age groups; (4) calculating the overall quality score of each playground and proposing policy and design recommendations for improvement.The findings highlight significant deficiencies in accessibility, safety, auxiliary equipment, and the diversity of play elements, all of which influence children's well-being. A critical concern is the absence of inclusive play structures for children with disabilities and the lack of interactive play elements, which limit the developmental opportunities these spaces provide. The study emphasizes the need for policy interventions and urban design enhancements to create more inclusive, safer, and developmentally enriching playgrounds, supporting broader strategies that prioritize children's well-being.
Keywords: Playground suitability; Children's well-being; Weighted criteria method; Urban play environment; T & uuml;rkiye